Application of an oral health prevention program in Mexican elementary schools - Rosa María Cruz Martínez; Gerardo Alfonso Saucedo Campos; Efrén Raúl Ponce Rosas; Alberto González Pedraza Avilés (Editorial Ciencias Médicas, 2018)
Introduction: the high prevalence of oral disease among school children has a great impact on their health, hence the need to develop control programs and strategies at public policy level. Objective: evaluate the Oral Health Program for Mexican elementary school children. Methods: a community intervention study was conducted in two public elementary schools from the Ministry of Health in the borough of Tlalpan, Mexico City. The study sample was composed of 111 fifth grade students, 53 from Río Pánuco morning session public school as intervention group with application of the oral health program (work group), and 58 from Ignacio Rodríguez Galván school, without intervention (control group). All students were examined to determine the rate of decay, loss, temporary fillings and permanent teeth, and the community periodontal index. Inferential statistical analysis was based on Mann-Whitney U and Pearson's chi-square, with a significance level of 0.05. Data were processed with the statistical software SPSS version 22. Results: mean age was 10.9 at the intervention school and 10.8 at the control school. With respect to the primary dentition index, the average of decayed teeth was 0.49 (CI 95 % 0.07-0.91) for the school with the intervention program, and 1.10 (CI 95 % 0.70-1.51) for the school without intervention, with significant statistical differences (p= 0.003). As to the community periodontal index, 92.4 % of the children were healthy at the school with the intervention program, and 70.68 % were healthy at the school without intervention, with a significant statistical difference (p= 0.003). Conclusions: results show that the program is effective, since the school children intervened are in better oral health conditions than those in the control group, and the difference is clinically relevant.